2001
DOI: 10.1128/mcb.21.7.2570-2580.2001
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor-Like Repeats Mediate Lateral and Reciprocal Interactions of Ep-CAM Molecules in Homophilic Adhesions

Abstract: Ep-CAM is a new type of cell adhesion molecule (CAM) which does not structurally resemble the members of the four major families (cadherins, integrins, selectins, and CAMs of the immunoglobulin superfamily) and mediates Ca 2؉ -independent, homophilic adhesions. The extracellular domain of Ep-CAM consists of a cysteine-rich region, containing two type II epidermal growth factor (EGF)-like repeats, followed by a cysteine-poor region. We generated mutated Ep-CAM forms with various deletions in the extracellular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(167 citation statements)
references
References 43 publications
5
157
1
1
Order By: Relevance
“…Binding studies with truncated Ep-CAM showed that both 323/A3 and edrecolomab do bind the immunodominant EGFlike domain I of Ep-CAM. 10,24 We infer from the competition data that M79 and MT201 also recognized this subdomain, although this conclusion may require further support from binding studies using truncated Ep-CAM versions.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Binding studies with truncated Ep-CAM showed that both 323/A3 and edrecolomab do bind the immunodominant EGFlike domain I of Ep-CAM. 10,24 We infer from the competition data that M79 and MT201 also recognized this subdomain, although this conclusion may require further support from binding studies using truncated Ep-CAM versions.…”
Section: Discussionmentioning
confidence: 86%
“…For 323/A3 and edrecolomab, the subdomain of Ep-CAM was previously determined to be the immunodominant, outer EGF-like domain I. 24 Because both M79 and 323/A3 did compete efficiently with all other antibodies, it appears they recognized epitopes on the same Ep-CAM subdomain that are overlapping with those recognized by MT201 and edrecolomab. Within this Ep-CAM subdomain, MT201 and edrecolomab apparently recognized the most distant epitopes, as was evident from their weakest cross-competition among the 4 anti-Ep-CAM mAbs tested.…”
Section: Epitope Recognition Of Mt201 Relative To Other Anti-ep-cam Mabsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact function of these domains is still unclear, but they have been reported, e.g. to mediate homophilic and heterophilic protein-protein interactions [19,20]. Recently, a similar domain in a homologous molecule Stabilin-2 has been shown to play a key role in the clearance of aged and apoptotic cells through recognition of the exposed phosphatidyl serine (PS) on the cell surface [21].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Ep-CAM in human adult tissues is largely restricted to epithelial cells, with a few exceptions such as squamous epithelium and some epithelium-derived cells such as hepatocytes [1]. This antigen is believed to be involved in homotypic calciumindependent cell-cell adhesion, as one of several classes of intercellular adhesion molecules [2]. Additional studies demonstrated Ep-CAM colocalization with the intracellular actin cytoskeleton, and also found that selective mutational analysis of the cytoplasmic domain resulted in lack of adhesion [3].…”
Section: Introductionmentioning
confidence: 99%